2024
DOI: 10.1039/d3ta07050f
|View full text |Cite
|
Sign up to set email alerts
|

Designing thickness-insensitive cathode interlayers via constructing noncovalently conformational locks for highly efficient non-fullerene organic solar cells

Haolan Zheng,
Lin Hu,
Xiaotian Hu
et al.

Abstract: Two novel water/alcohol-soluble conjugated polyelectrolytes, PF-TT and PF-BDT, have been designed and synthesized as cathode interlayer (CIL) for highly efficient non-fullerene organic solar cells (OSCs). They both have superior charge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The dihedral angle between the D and A moieties is one of the key factors influencing the electronic structures, photophysical properties, self-assembling behaviors, molecular packing motifs, and charge carrier mobilities of π-conjugated systems . It has been demonstrated that the through-space noncovalent conformational locks strategy has been employed with great success to design highly planar and single bond-linked π-conjugated D–A systems for organic electronics . Meanwhile, the other effective approach for manipulating the dihedral angle of conjugated backbone is the through-bond ring fusion strategy to construct fully fused polycyclic aromatic hydrocarbons (PAHs) .…”
mentioning
confidence: 99%
“…The dihedral angle between the D and A moieties is one of the key factors influencing the electronic structures, photophysical properties, self-assembling behaviors, molecular packing motifs, and charge carrier mobilities of π-conjugated systems . It has been demonstrated that the through-space noncovalent conformational locks strategy has been employed with great success to design highly planar and single bond-linked π-conjugated D–A systems for organic electronics . Meanwhile, the other effective approach for manipulating the dihedral angle of conjugated backbone is the through-bond ring fusion strategy to construct fully fused polycyclic aromatic hydrocarbons (PAHs) .…”
mentioning
confidence: 99%